Investigation of two o-hydroxy Schiff bases in terms of prototropy and radical scavenging activity - Albayrak Kaştaş, Çiğdem; Kaştaş, Gökhan; Güder, Aytaç; Gür, Mahmut; Muğlu, Halit; Büyükgüngör, Orhan (Elsevier BV, 2017)
Abstract Two Schiff bases, namely (E)-4,6-dibromo-3-methoxy-2-[(phenylimino)methyl]phenol (1) and (Z)-2,4-dibromo-6-[(4-buthylphenylamino)methylene]-5-methoxycyclohexa-2,4-dienone (2), have been investigated by considering solvent, substituent and temperature dependence of prototropy, and scavenging activities. Experimental (X-ray diffraction, UV–vis and NMR) and computational (DFT) techniques have been used to obtain key data on prototropy and other properties of interest. X-ray and UV–vis results underline the variability in the structural preferences of the compounds with respect to the phase and solvent media conditions. This kind of tautomeric behavior has been elaborated by 1H NMR and 13C NMR experiments performed at room and low temperatures. Radical scavenging properties of two compounds have been probed for their usage potentials as therapeutic agent and ingredient in medicinal and food industries, respectively. For this purpose, three different test methods (DPPH, ABTS•+ and DMPD•+) have been used. It has been found from in vivo and in vitro studies that the compound 2 could be interesting as an active component in pharmaceutical industry or as an additive in food industry when its antiradical activity is considered.
Keywords: X-ray; Schiff base; Scavenging activity; Keto-amine; Phenol-imine; NMR; Tautomerism